Bimbingan Teknik Penulisan Karya Ilmiah untuk Mahasiswa Universitas Islam Indragiri (UNISI) Tembilahan - Ferdinan Ferdinan; Sri Erdawati; Saiin Saiin; M. Ridhwan; Ahmad Ahmad (STAI Auliaurrasyidin Tembilahan, 2020)
This study discussed the Technical Supervision for Writing Scientific Papers held at the Islamic University of Indragiri (UNISI) Tembilahan. This activity was important because it can educate, train, and supervise students to write based on scientific writing procedures. The purpose of this activity was to provide practical supervision for students, they can apply these supervision techniques when writing papers, research proposals, research reports, writing resumes, and book reviews, especially writing a final project that must be accomplished before graduation. This activity was very welcomed enthusiastically by students because they became more aware of the definition of scientific writing, its objectives, its benefits, its characteristics, and knowing techniques and steps about scientific writing.